Pengaruh Pelayanan dan Prosedur Perbankan Terhadap Keputusan Nasabah Dalam Mengambil Kredit Pada BPR Hasil Jaya Sentosa Surabaya - Eko Budiyanto; Dewita A Batmanlussy (Fakultas Ekonomi Universitas Yos Soedarso, 2021)
The population of this study were all customers who took credit at BPRhasil Jaya Sentosa Surabaya, totaling 11,517 people. The sampling technique for this study used a simple random sampling technique with a total sample of 240 respondents. The variables in this study are Customer Decisions in Taking Credit (Y), Services (X1) and Procedures for Granting Credit (X2). Data collection techniques using a questionnaire. Test the validity of the instrument using the product moment technique and test the reliability using the Alpha Cronbach formula. Analysis prerequisite tests include normality tests and linearity tests. Based on the results of the research analysis shows (1) there is a positive influence of banking image on customer decisions in taking credit at BPRhasil Jaya Sentosa Surabaya with a value of R = 0.036 and a value of R2 = 0.001, (2) a positive influence of banking image on customer decisions in taking credit with service as a Moderating Variable at PD BPR Bank Sidoarjo with a value of R=0.041 and a value of R2=0.002, (3) The Positive Effect of Banking Image on Customer Decisions in Taking Credit with Credit Procedures as a Moderating Variable at BPR Prestasi Jaya Sentosa Surabaya Value R=0.090 and R2=0.008. Keywords: Customer Decisions in Taking Credit; Credit Services and Procedures.